Rate equations for nitrogen molecules in ultrashort and intense x-ray pulses - Liu, Ji-Cai; Berrah, Nora; Cederbaum, Lorenz S.; Cryan, James P.; Glownia, James M.; Schafer, Kenneth J.; Buth, Christian (Journal of physics. B, Atomic, molecular and optical physics, 2016)
We study theoretically the quantum dynamics of nitrogen molecules (N2) exposed to intense and ultrafast x-rays at a wavelength of ( photon energy) from the Linac Coherent Light Source (LCLS) free electron laser. Molecular rate equations are derived to describe the intertwined photoionization, decay, and dissociation processes occurring for N2. This model complements our earlier phenomenological approaches, the single-atom, symmetric-sharing, and fragmentation-matrix models of 2012 (J. Chem. Phys. 136 214310). Our rate-equations are used to obtain the effective pulse energy at the sample and the time scale for the dissociation of the metastable dication . This leads to a very good agreement between the theoretically and experimentally determined ion yields and, consequently, the average charge states. The effective pulse energy is found to decrease with shortening pulse duration. This variation together with a change in the molecular fragmentation pattern and frustrated absorption—an effect that reduces absorption of x-rays due to (double) core hole formation—are the causes for the drop of the average charge state with shortening LCLS pulse duration discovered previously.
Gesehen am 27.05.2020